RESPONS PERTUMBUHAN TANAMAN JARAK PAGAR (Jatropha curcas L.) AKIBAT PEMBERIAN ASAM HUMAT DAN FUNGI MIKORIZA ARBUSKULA - Asri Mulya Ashari; Cucu Suherman; Anne Nuraini (Jurnal Agroekoteknologi, 2017)
Castor oil plant (Jatropha curcas L.) is one of the types of plants that can be alternative energy sources replacement fuel. Plant spacing the Castor oil plant Jatropha curcas belongs to the shrubs that come from Central America, Mexico and spread to Africa and Asia. Process presses the castor bean castor oil can produce Jatropha curcas called crude Jatropha curcas oil and can be used as a substitute for kerosene for household use. This research has been carried out at the experimental Ciparanje, Faculty of Agriculture, University of Padjadjaran. In Jatinangor Sumedang reached places with an altitude of 829 m above sea level in June 2016-January 2017. The goal of the research is to obtain doses of the humic acid and dose of Asrbuskula Mycorrhiza Fungi and effect on plant growth the distance the fence. This research used a Randomized Completely Block Design as Factorial Design Patterns Group consists of two factors and three replicates. The first factor is the second factor of the humic acid and Asrbuskula Mycorrhiza Fungi. The observations were analyzed statistically using test method F. Test Duncan's Multiple Range Test done when F calculate the treatment is greater than F table 5%. The results showed that humic acid was accompanied by Asrbuskula Mycorrhiza Fungi provides high-impact on crops, the diameter of the heading, rate of growing plants, the relative rate of plants, broad leaves, and net assimilation rate. A dose of 20 g humic acid which carries 5 g Asrbuskula Mycorrhiza Fungi was the best dose for plant growth the distance the fence.Keywords: Fences, Humic acid, Mycorrhiza Arbuskula Fungi